(untitled) (International Journal of Engineering and Computer Science, 2014)
The use of fiber reinforced polymer (FRP) is becoming a widely accepted solution for repairing and strengthening in the field of civil engineering around the world. The shear strength of a reinforced concrete beam can be extensively increased by application of carbon (CFRP), glass (GFRP) and aramid (AFRP) FRP sheets adhesively bonded to the shear zone of the beam. This paper deals with Theoretical and experimental investigation for enhancing the shear capacity of RC beams using Glass fiber reinforced polymers (GFRP) polymers